Inside single party government : the UK Conservative Party 1975-1990 - Garry, John (Trinity College (Dublin, Ireland). Department of Political Science, 2001)
This thesis tells the story of the UK change of prime minister in 1990 using a policy-based multi-dimensional model of intra-party competition. Specifically, it focuses on Margaret Thatcher's fall in 1990 from the position of party leader and prime minister and her replacement by John Major. This thesis develops a model of intra-party competition and applies it to the UK Conservative Party 1975-90. The model isolates the unique impact of salience change on actor's preferences over real world alternative prime ministers. I argue that in UK Conservative politics in the 1980s there was a change in the relative salience of key policy areas - there was a rise in the importance of EU policy and a consequent decline in the relative importance of domestic economic policy. I argue that change in relative salience of policy dimensions can impact on the incumbent party leader's support base in the party, leaving her more vulnerable to challenge from rivals within the party. The thesis illustrates the potential of models of party competition based on a non-unitary actor assumption, which are very rare in the literature.
Keywords: Politics, Ph.D.; Ph.D. Trinity College Dublin